(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The aim of the paper is to study the theoretical and applied principles of current state and prospects of populations’ social protection development in Ukraine. The article deals with theoretical and practical aspects, specificity and peculiarities of formation of populations’ social protection in Ukraine and Volyn region. The program of housing subsidies, payment of state social assistance, sanatorium and resort health improvement, preferential support, as well as wage arrears are analyzed in this work. The social protection of the population in general, as well as its special categories are considered (such as invalids, newborns, internally displaced and demobilized persons, participants of the united forces operation and the Revolution of Dignity including members of their families). The basic indicators of social protection of the region are systematized and their dynamics are determined. The main problems of populations’ social protection are singled out, as well as priority directions of its development on the national and regional levels are formed. The falsehood of the existing system of housing subsidies is substantiated, its main disadvantages and alternatives to the budget funds use are indicated. The populations’ social protection should take place within the framework of the state poverty reduction strategy, which should take into account the following priority directions of its development: the regulation of the legislative framework (in particular the settlement of controversial provisions and the concentration of the whole regulations in one Social Code); improvement of social assistance system, in particular adherence to the principle of targeting social benefits with a gradual refusal of general benefits and subsidies; creating conditions for citizens’ self-defense, including opportunities for employment with decent real wages; effective redistribution of funds from large businesses in favor of ordinary employees; provision of financing parity for social protection programs (in particular, creation of a three-level pension system and compulsory health insurance, increasing the role of local budgets and self-government bodies in social security, promoting charitable programs, social-ethical marketing actions and corporate social responsibility).